Educational inequality in Vietnam - DUONG, Linh Thuy (KDI School, 2015)
Education is the key prominent in the development of a nation. Despite the fact that Vietnam has made significant achievement in universal primary education, disadvantage groups including poor households, ethnic minorities and disable people still lag behind in their education achievement. This thesis will figure out the practice of educational inequality in Vietnam in different aspects such as gender, ethnicity and generation. Using panel data from Vietnam Household Living Standard Survey from 2010 to 2012, it provides evidence of inequality in education system based on Gini coefficient for different regions, ethnic groups and generation. Then, this thesis examines the relationship between education attainment and family background, gender, ethnicity, and region disparities. As expected, there are different levels of educational inequality among groups, especially between Kinh ethnic and other ethnic minorities. Besides, socioeconomic status was found as the most important variable that influences education attainment, followed by regional disparity.
Thesis(Master) --KDI School:Master of Public Policy,2015